Evaluations of the pathophysiology and reproductive pathology of bucks inoculated with Corynebacterium pseudotuberculosis and its immunogen mycolic acid extract - Mohamad Nor, Nur Faeza (2019)
Corynebacterium pseudotuberculosis is the causative agent of caseous lymphadenitis, a chronic disease of sheep and goats, characterized by the formation of suppurative abscesses in superficial and visceral lymph nodes and internal organs of small ruminants. Little is known about the male goat`s reproductive pathophysiology inoculated with Corynebacterium pseudotuberculois and its immunogen mycolic acid extract. Hence, this study was designed to determine the concentration of testosterone hormone and proinflammatory cytokines of the experimental animals and to determine the histopathological effectof male reproductive organs and the associated lymph nodes. A total of 12 bucks, divided into 3 treatment groups of equal numbers (4 goats per group) were selected in this study.